Analysis of China's oil and gas consumption under different scenarios toward 2050: An integrated modeling. (15th March 2020) - Pan, Xunzhang; Wang, Lining; Dai, Jiaquan; Zhang, Qi; Peng, Tianduo; Chen, Wenying
Abstract: China's oil and gas consumption, which is not only significant to the industry but also related with national energy security, faces uncertainties in the future. This paper analyzes China's oil and gas consumption under five representative scenarios toward 2050 using an integrated modeling. In the Nationally Determined Contribution (NDC) scenario, China's oil consumption peaks at 705 million tons by 2035, and gas consumption ramps steadily up to reach 780 billion cubic meters by 2050. Oil provides 18% of China's primary energy by 2030 and 15% by 2050, and gas 14% by 2030 and 17% by 2050. The 2 °C and the 1.5 °C scenarios control China's 2050 oil consumption to 10% and 45% below the NDC level, respectively. Interestingly, more stringent mitigation tends to upscale China's gas consumption before 2040. Compared with the NDC scenario, the oil-price scenarios present limited influences on China's total energy consumption and end-use electrification but mainly feature a substitution between oil, gas and coal, non-fossil energy. Particularly, across our scenarios, China's oil import dependence is projected to largely fluctuate around 70% toward 2050, and gas import dependence to reach 50–60% beyond 2030, implying a continuously high risk of energy resource supply and national energy security. Highlights: China's oil and gas consumption is analyzed using an integrated modeling. Oil consumption is estimated to peak by 2035 at 705 mtoe in the NDC scenario. More stringent mitigation requires more gas consumption before 2040. Oil and gas tend to still play an important role in the coming three decades. Import dependence implies a continuously high risk of national energy security.